Direct identification and susceptibility testing of positive blood cultures using high speed cold centrifugation and Vitek II system. Issue 3 (May 2017) - Bazzi, Ali M.; Rabaan, Ali A.; Fawarah, Mahmoud M.; Al-Tawfiq, Jaffar A.
Summary: Compared to routine isolated colony-based methods, direct testing of bacterial pellets from positive blood cultures reduces turnaround time for reporting of antibiotic susceptibility. The aim of this study was to compare the accuracy, and precision, of a rapid method for direct identification and susceptibility testing of blood cultures with the routine method used in our laboratory, using Vitek 2. A total of 60 isolates were evaluated using the candidate and the routine method. The candidate method had 100% accuracy for the identification of Gram negative bacteria, Staphylococcus and Enterococcus, 50% for Streptococcus and 33.3% for Corynebacterium species. Susceptibility testing of Gram negative isolates yielded 98–100% essential agreement. For Staphylococcus and Enterococcus isolates, essential agreement was 100% for 17 antibiotics except for moxifloxacin. Direct testing of blood culture samples with Vitek 2 produced reliable identification and susceptibility results 18–24 h sooner for aerobic/anaerobic facultative Gram-negative bacteria and Gram-positive Staphylococcus and Enterococcus strains.